Astrology : the divine science - Moore, Marcia; Douglas, Mark. (York Harbor, Me. : Arcane Publications, 1978)
This unique book will instruct the newcomer, enlighten the expert, and extend the boundaries of contemporary thought. It contains all the information you need to become an expert astrologer-including instructions for casting and interpreting horoscopes. The authors present astrology in a readable manner that enables you to understand basic character, human relationships, and life-trends. Their commonsense approach tells how you can effectively direct the forces of your destiny by assessing the nature of the assets and liabilities with which you were born.
Includes index.
Bibliography: p. 765-769.
Keywords: Astrology